Nuevos antecedentes en la distribución y ecología de Botrychium dusenii (H. Christ.) Alston (Ophioglossaceae) asociado a ambientes antropogénicos de la provincia de Coyhaique, Región de Aysén, Chile - BRAVO-MONASTERIO, PABLO; PEÑAILILLO, PATRICIO; FAJARDO, ALEX (Gayana Botánica, 2012)
Conducting botanical and ecological explorations with the objective of studying the floristic composition of post-fire communities in the Aysén Region, we found new regional records of the fern Botrychium dusenii (H. Christ.) Alston (Ophioglossaceae). These findings, that extend the north limit of the species distribution, occurred in open areas affected by historical human-provoked fires (happening between 1950 and 1960) during the regional process of colonization.